Striving to Make a Positive Difference: School Nurses' Experiences of Promoting the Health and Well-Being of Adolescent Girls. (October 2014) - Larsson, Margaretha; Björk, Maria; Ekebergh, Margaretha; Sundler, Annelie Johansson
In Sweden, school nurses are part of the School Health Service with the main objective of health promotion to support students' health and attainment of educational goals. The aim in this phenomenological study was to illuminate the experiences of school nurses in promoting the health and well-being of adolescent girls. Seventeen school nurses were interviewed, both in groups and individually, to facilitate personal disclosure and expressions from their lived experiences. To achieve their goal of improving the health of adolescent girls, school nurses require flexibility in their approach and in endeavoring to make a positive difference they experience many challenges. This study concluded that school nurses can tactfully provide adolescent girls with knowledge and health guidance adjusted to individual needs and empowering the individual girl to participate in her own health process.